Molecular Survey of Viral and Bacterial Causes of Childhood Diarrhea in Khartoum State, Sudan - Adam, Mosab A.; Wang, Ji; Enan, Khalid-A.; Shen, Hongwei; Wang, Hao; El Hussein, Abdel R.; Musa, Azza B.; Khidir, Isam M.; Ma, Xuejun (Frontiers in Microbiology, 2018)
Molecular Survey of viral and bacterial causes of childhood diarrhea in Khartoum State, Sudan Diarrheal diseases are a major public health problem for children in developing countries. Knowledge of causative agents that cause diarrheal illness is essential in public health measures to prevent and control these diseases. Published studies regarding the problem of childhood diarrhea in Sudan is scanty. This study investigates viral and bacterial etiology and related clinical and epidemiological factors in children with acute diarrhea in Khartoum State, Sudan. A total of 437 fecal samples were collected from hospitalized children less than five years old with acute diarrhea, viral and bacterial pathogens were investigated by using two-tube multiplex RT-PCR, direct sequencing determined genotypes of adenovirus and bocavirus. .A two-tube multiplex PCR identified viral diarrhea in 79 cases (18%), bacterial diarrhea in 49 cases (11.2%) ;the mixed infection of more than one pathogen were detected in 19 samples (4.3%). Rotavirus (10.2%) was predominantly detected followed by norovirus G2 (4%), adenovirus (1.6 %), bocavirus (1%) and norovirus G1 (0.9%). Infection with an astrovirus was not detected in this study. The Shigella –Enteroinvasive E.coli (EIEC) (8.9%) was the predominant bacterial pathogen followed by Vibrio parahaemolyticus (0.9%), enterohaemorrhagic E.coli (EHEC) –Enteropathogenic E. coli (EPEC) (0.6%) and Salmonella enteritidis (0.6%). V.cholerae, Yersinia enterocolitica, and Campylobacter jejuni were not detected in this study. An adenovirus phylogenetic tree showed that these Sudanese strains belonged to adenovirus genotype 41; there were slight differences between adenoviruses genotype 41 identified. Bocavirus phylogenetic tree indicated that the Sudanese strains belonged to two different clades within human bocavirus 1. Our findings represent the first report that adenovirus 41 is a cause of diarrhea in Sudan and that human bocavirus 1 is the principal bocavirus strain circulating in Sudan. In conclusion: This is the first comprehensive report to elaborate the pathogen spectrum associated with childhood diarrhea in Khartoum State, Sudan. The results obtained in the present study highlighted the current epidemic situation, the diverse pathogens related to childhood diarrhea, and the importance and the urgency of taking appropriate intervention measures in Khartoum State, Sudan.